PTH-100 Utility Of Eus-guided Fine Needle Aspiration Of Pancreatic Cystic Lesions. (9th June 2014) - Donnelly, MC; Cheng, P; Leeds, JS
Abstract : Introduction: At least 1% of hospitalised patients will have a pancreatic cystic lesion on cross sectional imaging 1 . Differentiation of benign and potentially malignant/malignant pancreatic cystic lesions using conventional radiology and prior to surgery is difficult. Endoscopic ultrasound (EUS) guided fine needle aspiration (FNA) is considered safe, yet there is relatively limited data on the clinical utility of EUS in this setting or its complication rate. Methods: Retrospectively, 43 consecutive patients (F = 26, M = 17, mean age 63) undergoing EUS-FNA of a pancreatic cystic lesion (no. procedures = 46) following abnormal imaging were identified from an institutionally approved database. Data collected included pre-EUS imaging, EUS findings, number of passes, cyst fluid CEA, amylase and cytology, sedation requirements, complication rate and six month follow up where available. Results: 44 procedures provided sufficient information for further analysis. At EUS, 23 cystic lesions appeared benign and 21 premalignant/malignant. Median CEA (ug/L) in the benign group was 6 vs. 2234 in the malignant group; p < 0.001. Median amylase (U/L) in the benign group was 2989, versus 2795 in the malignant group; p = 1.0. In the malignant group, 4/21(19%) had positive cytology. In the benign group, 16/23 (69.5%) had no malignant cells. Cytology was insufficient for analysis in 4/23 of benign appearing lesions, and 3/21 in malignant appearing lesions. Average midazolam dose was 3.3 mg, and average pethidine dose 27.9 mg. Complication rate was 4% (n = 2), with one patient experiencing severe abdominal pain (serum amylase normal) and another having a documented bile leak. Availability of follow up data was limited by patients returning to their secondary care referral centres. 4 patients proceeded to surgery and had resection pathology available. Of these, 3 patients had confirmed malignant IPMN (one patient had no cyst fluid for analysis, one had raised CEA and no available cytology, and one had suggestive cytology but no CEA analysis). The fourth patient had a mucinous cystadenoma, with mucin aspirated at FNA but no CEA analysed. Conclusion: EUS provides useful information with regards to the macroscopic appearances of pancreatic cystic lesions. FNA is safe and allows the addition of fluid CEA as a useful marker for malignancy. Negative cytology does not exclude malignancy but false positives are rare. Difficulty in aspirating fluid should be considered suspicious. Reference: 1 Khalid A, Brugge W. ACG Practice guidelines for the diagnosis and management of neoplastic pancreatic cysts. Am Journ Gastroenterol (2007);102:2339-2349 Disclosure of Interest: None Declared.